2007
DOI: 10.1007/s10529-007-9478-3
|View full text |Cite
|
Sign up to set email alerts
|

Novel chimeric anti-ricin antibody C4C13 with neutralizing activity against ricin toxicity

Abstract: So far, no specific therapeutic agent is available for the treatment of ricin intoxication. Here, V(H) and V(L) genes were cloned from a hybridoma cell line secreting anti-ricin mAb 4C13, which could neutralize the toxicity of ricin. A chimeric antibody, c4C13, containing 4C13 mAb variable region genes fused to human constant region genes (gamma 1, kappa), was constructed. C4C13 retained the binding activity and recognized the same, or a closely related, epitope as the original mouse antibody. Furthermore, c4C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Once ricin has been internalized into the cells, it cannot be inactivated by antibodies, limiting the therapeutic window. In order to circumvent the side effects of animal antisera (anaphylaxis, serum sickness), recent research focused on humanized monoclonal antibodies or recombinant antibodies [325,326]. …”
Section: Treatment and Vaccinationmentioning
confidence: 99%
“…Once ricin has been internalized into the cells, it cannot be inactivated by antibodies, limiting the therapeutic window. In order to circumvent the side effects of animal antisera (anaphylaxis, serum sickness), recent research focused on humanized monoclonal antibodies or recombinant antibodies [325,326]. …”
Section: Treatment and Vaccinationmentioning
confidence: 99%
“…Some studies however, have been carried out to evaluate the potency and timeframe for anti-ricin antibody-based passive immunization following exposure of experimental animals to lethal doses of ricin (Maddaloni et al, 2004;Wang et al, 2006Wang et al, , 2007Prigent et al, 2011). Recently, we evaluated the efficiency of postexposure treatment of pulmonary ricinosis by polyclonal antiricin antibodies, and demonstrated that survival rates can be increased by combining the antidotal treatment with the antiinflammatory compound, doxycycline (Gal et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous groups, including ours, have reported that immunization of mice with RTB elicits a mixture of ricin toxin neutralizing and non-neutralizing antibodies ( Table S1 ) [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32]. In an effort to identify the regions (or sub-domains) of RTB that are important in eliciting protective immunity to ricin, we recently produced and characterized a collection of two neutralizing and four non-neutralizing RTB-specific murine monoclonal antibodies (mAbs) ( Fig.…”
Section: Introductionmentioning
confidence: 99%